2015
DOI: 10.1007/s10903-015-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Literacy in Predicting Multiple Healthcare Outcomes Among Hispanics in a Nationally Representative Sample: A Comparative Analysis by English Proficiency Levels

Abstract: Health literacy (HL) research among Hispanics currently focuses on individuals with limited English proficiency but impacts of HL on healthcare outcomes among other English language proficiency groups is relatively unknown. Regression models assessed associations between HL and healthcare outcomes for Hispanics overall (n = 4013) and for proficiency level sub-populations using the 2007 Pew Hispanic Health Survey. Overall, Hispanics with adequate HL percieved US medical care as "excellent," were more satisfied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…Patient‐centered communication and culturally‐informed care are necessary for effective patient–provider interaction and rapport (Cuevas, O'brien, & Saha, ). Limited language skills affect their interaction with the health‐care system; for example, when asking questions to health‐care providers, poor language skills resulted in minimum information exchange, limited health literacy, and poor knowledge of disease management (Sarkar, Asti, Nacion, & Chisolm, ). Results of a study on Asians living in England revealed a significant association between poorer English language skills and elevated, undetected blood sugar levels and blood pressure among Bangladeshis and Pakistanis.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐centered communication and culturally‐informed care are necessary for effective patient–provider interaction and rapport (Cuevas, O'brien, & Saha, ). Limited language skills affect their interaction with the health‐care system; for example, when asking questions to health‐care providers, poor language skills resulted in minimum information exchange, limited health literacy, and poor knowledge of disease management (Sarkar, Asti, Nacion, & Chisolm, ). Results of a study on Asians living in England revealed a significant association between poorer English language skills and elevated, undetected blood sugar levels and blood pressure among Bangladeshis and Pakistanis.…”
Section: Discussionmentioning
confidence: 99%
“…Minority women and women of low SES are less likely to have timely mammograms and adequate follow‐up for abnormal mammograms . Discrepancies in presentation and treatment are also observed in LEP patients, as language barriers are associated with lower health literacy, limited patient participation, shared decision making and play a significant role in inadequate health care delivery . These in turn influence receipt of surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…11 Discrepancies in presentation and treatment are also observed in LEP patients, as language barriers are associated with lower health literacy, limited patient participation, shared decision making and play a significant role in inadequate health care delivery. 15,16 These in turn influence receipt of surgical treatment. African American women are less likely to receive breast conserving surgery, compared to Caucasian women.…”
mentioning
confidence: 99%
“…Studies performed by the National Assessment of Adult Literacy (NAAL) and the Pew Research Center have substantiated that Hispanics have the lowest levels of health literacy when compared to other minority groups in the US. The decreased level of health literacy in this population is associated with erroneous use of medications and decreased medication adherence (Sarkar et al, 2016). Research findings have corroborated that culture may play a crucial role in influencing individual beliefs about medication usage and adherence.…”
Section: !mentioning
confidence: 68%
“…The Hispanic population, especially, is widely affected by the presence of LEP. Presently, the Hispanics are believed to be the largest and most rapidly growing minority group in the United States (US), accounting for 54 million individuals and comprising 17% of the country's population (Schembri & Ghaddar, 2017;Sarkar, Asti, Nacion, & Chisolm, 2016).…”
Section: Introductionmentioning
confidence: 99%